Automated Measurement of Intracranial Volume Using Three-Dimensional Photography. Issue 3 (September 2020) - Tu, Liyun; Porras, Antonio R.; Enquobahrie, Andinet; Buck, B.S., Graham C.; Tsering, M.S., Deki; Horvath, Samantha; Keating, Robert; Oh, Albert K.; Rogers, Gary F.; George Linguraru, Marius
Abstract : Background: Current methods to analyze three-dimensional photography do not quantify intracranial volume, an important metric of development. This study presents the first noninvasive, radiation-free, accurate, and reproducible method to quantify intracranial volume from three-dimensional photography. Methods: In this retrospective study, cranial bones and head skin were automatically segmented from computed tomographic images of 575 subjects without cranial abnormality (average age, 5 ± 5 years; range, 0 to 16 years). The intracranial volume and the head volume were measured at the cranial vault region, and their relation was modeled by polynomial regression, also accounting for age and sex. Then, the regression model was used to estimate the intracranial volume of 30 independent pediatric patients from their head volume measured using three-dimensional photography. Evaluation was performed by comparing the estimated intracranial volume with the true intracranial volume of these patients computed from paired computed tomographic images; two growth models were used to compensate for the time gap between computed tomographic and three-dimensional photography. Results: The regression model estimated the intracranial volume of the normative population from the head volume calculated from computed tomographic images with an average error of 3.81 ± 3.15 percent ( p = 0.93) and a correlation ( R 2 ) of 0.96. The authors obtained an average error of 4.07 ± 3.01 percent ( p = 0.57) in estimating the intracranial volume of the patients from three-dimensional photography using the regression model. Conclusion: Three-dimensional photography with image analysis provides measurement of intracranial volume with clinically acceptable accuracy, thus offering a noninvasive, precise, and reproducible method to evaluate normal and abnormal brain development in young children. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, V.